THE APPLICATION OF FINTECH IN THE OPERATION OF ISLAMIC BANKING FOCUSSING ON ISLAMIC DOCUMENTATION: POST-COVID-19 (International Seminar on Syariah and Law (INSLA), 2025)
FinTech is innovation, and it is developing rapidly as part of current human need dealing with financial transactions in daily life, embracing the banking industry as convenience instruments to the consumers. Adapting FinTechin Islamic banking is challenges in terms of Shariah-compliant as the essential elements of riba',maysir, and gharar prohibited from forming part of the FinTechcomponent. Islamic finance institutions in the world face problem in dealing with financial transactions as well as saviour during pandemic COVID 19, where most countries in the world are affected and declared lockdown as an emergency solution to cutthe chain of COVID 19. Concerning the pandemic crisis, problems on the operation of Islamic banking adopted Islamic Fintech need to explore, which also concerning the conduct of legal firms in managing Islamic banking documentation. The objective of this paper is to identify the application of Islamic fintech in Islamic banking, the legal framework of Islamic fintech, issues in managing the operation and Islamic banking documentation at legal firms, and analysethe suitability of Islamic fintech in the service of Islamic banking during the Movement Control Order. The methodology used in attaining the objectives is qualitative by utilizing the library as the data centre, review the journals and articles, including collecting data from books and available reports. As a result of the study, the paper suggested new norms need a new approach by Islamic finance and any legal institution since the operation heavily relies on the adherence to Syariah requirements and guidelines issued by Bank Negara Malaysia and Security Commission. The support from the government in providing an adequate legal framework for fintech's instrument to operate needs attention, and consultation among the experts is much welcome by the fintech community.